2022
DOI: 10.3389/fnhum.2022.1051793
|View full text |Cite|
|
Sign up to set email alerts
|

Twenty-four-hour time-use composition and cognitive function in older adults: cross-sectional findings of the ACTIVate study

Abstract: IntroductionPhysical activity, sedentary behaviour and sleep are associated with cognitive function in older adults. However, these behaviours are not independent, but instead make up exclusive and exhaustive components of the 24-h day. Few studies have investigated associations between 24-h time-use composition and cognitive function in older adults. Of these, none have considered how the quality of sleep, or the context of physical activity and sedentary behaviour may impact these relationships. This study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 63 publications
0
12
1
Order By: Relevance
“…First, the sample used in the current study was recruited for a longitudinal study which aims to map differences in lifestyle (time use and diet) against changes in cognitive function, therefore at baseline participants were required to be healthy with no cognitive impairment. Despite best efforts to recruit participants across diverse lifestyle profiles, the sample had high cognitive function (mean score on Addenbrooke’s Cognitive Examination III at baseline was approximately 95/100 in the ACTIVate sample [ 28 ]), participants were physically active (mean total PA per day = 4.5 h), and there was little variability in time-use composition at baseline across the sample (see Fig. 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…First, the sample used in the current study was recruited for a longitudinal study which aims to map differences in lifestyle (time use and diet) against changes in cognitive function, therefore at baseline participants were required to be healthy with no cognitive impairment. Despite best efforts to recruit participants across diverse lifestyle profiles, the sample had high cognitive function (mean score on Addenbrooke’s Cognitive Examination III at baseline was approximately 95/100 in the ACTIVate sample [ 28 ]), participants were physically active (mean total PA per day = 4.5 h), and there was little variability in time-use composition at baseline across the sample (see Fig. 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it may be that those with smaller total grey matter volume were engaging in sedentary behaviours which are not beneficial for cognitive function (i.e., TV watching), whilst those with greater total grey matter volume were engaging in cognitively stimulating sedentary behaviours (i.e., computer use, reading), so reallocating time away from or towards sedentary behaviour, respectively, would be beneficial for executive function [ 17 ]. It should be noted that a previous study found no impact of sedentary behaviour context or sleep quality ratings on associations between 24-hour time-use composition and executive function in the ACTIVate cohort, but these analyses were conducted in the total sample only (and were not stratified by grey matter volume) [ 28 ]. Above all, it is important to note that the predicted differences in executive function resulting from each reallocation in this study were much smaller compared to those observed for long-term memory, so these findings should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations